Lolita's Death, Birth of Lilith: An Essay on Female Sexuality - Kron, Leposava; Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
We consider the tensions between two feminine sexual archetypes: child innocence of Lolita and oversexed power of Lilith. Developing a sexual self-concept is an important developmental step during adolescence. This is when adolescents try to make sense and organize their sexual experiences so that they understand the structures and underlying motivations for their sexual behavior. A new studies suggest that among teen and young adults femail, poor mental health has a reciprocal relationship with casual sex as each contribute to the other over time.